Retinal Vascular Fingerprints as Novel Biomarkers for Primary Angle Closure Disease Progression - Jin Wang, MD; Shumei Han, MD; Dapeng Mou, MD; Xin Tang, MD; Danli Shi, PhD; Mingguang He, MD; Chunyan Guo; Ningli Wang, MD, PhD; Ye Zhang, MD (Ophthalmology Science)
Purpose: To evaluate retinal vascular parameters across primary angle-closure disease (PACD) stages and explore their association with glaucomatous optic neuropathy (GON). Design: A cross-sectional, hospital-based study. Participants: We enrolled 638 eyes from 425 participants aged ≥40 years with PACD and further classified them into primary angle closure suspect (PACS), primary angle closure (PAC), and primary angle closure glaucoma (PACG) groups. Methods: Retinal vascular parameters were measured using the Retinal-based Microvascular Health Assessment System and compared between 3 groups. A multivariable logistic mixed effects model was used to identify factors associated with the presence of GON. Main Outcome Measures: Vessel caliber, tortuosity, complexity, and branching angle parameters. Results: No significant differences in retinal vascular parameters were found between PACS and PAC groups. Eyes in PACG showed significant vascular changes compared to PACS (P < 0.05). Elevated intraocular pressure (odds ratio [OR] = 2.44, P < 0.001), reduced arteriolar curve tortuosity (OR = 0.12, P = 0.002), arteriolar fractal dimension (OR = 0.08, P = 0.027), arteriolar branching angle (OR = 0.16, P = 0.004), and asymmetry ratio (OR = 0.10, P < 0.001 for artery and OR = 0.25, P = 0.023 for vein) were significantly associated with the presence of GON. Conclusions: Retinal “vascular geometric fingerprints” show significant alterations in eyes with PACG compared to PACS and are independently associated with the presence of GON. These findings offer new insights into the vascular changes in GON, and longitudinal studies are needed to determine their prognostic value and clinical utility in managing PACD. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.